Monitoring health inequalities in Barcelona. (30th September 2020) - Borrell, C; Artazcoz, L; Pasarín, I; Rodríguez-Sanz, M; Palència, L; Pérez, K
Abstract: In Spain, the Public Health Law approved in 2011 foresees the creation of a Surveillance System on Social Determinants of Health and Equity. However, although information on health inequalities has been reported in technical reports and scientific articles before, it is not until now with the change of the Spanish government the political will to set up the more strategic surveillance system approved and foreseen in 2011 is there. The change of government in some cities can be an opportunity to advance in the surveillance of health inequalities and policies to tackle them. In Barcelona, for instance, there is a wealth of information and research on health inequalities, but in the past health inequalities was not clearly prioritised on the political agenda. Hence, although health inequalities have been presented in many reports, a monitoring and surveillance system has not been available nor a prioritised task. This has now changed and as part of Spain's engagement in the Joint Action Health Equity Europe project (JAHEE) a system for Monitoring Health Inequalities in the city of Barcelona is being established. During the course of the JAHEE project the objectives of the system and target populations will be defined, sources of information and indicators identified, dissemination and evaluation structures set up before finally, in the next step, the system is to be implemented. The ambition is that the new monitoring system on health inequalities set up in Barcelona in its final form, will make out a part of the information systems of the Public Health Observatory of the city of Barcelona. In this presentation, we will learn more about the establishment, the content and the experiences gained while setting up the new monitoring system on health inequalities in Barcelona - from defining the objective of the system to implementing it.